Preliminary experience in endoscopic section of posterior urethral valves using the Holmium: YAG laser. Issue 3 (June 2022) - Gastaldi, Pauline; El-Khoury, Eliane; Haddad, Mirna; Mille, Eva; Dariel, Anne; Merrot, Thierry; Faure, Alice
Summary: Introduction: Refinements in endoscopic instrumentation, the widespread popularization of endourology and the minimal invasiveness of endoscopic approaches have led to evolving interest in expanding applications for their use and now include incision of posterior urethral valves (PUV). We aimed to report our paediatric experience of PUV incision with Holmium:YAG laser updating of the endoscopic technique, how we set parameters for the laser energy and provide some tips and tricks to increase the likelihood of completing treatment. Methods: A monocentric, prospective, continuous series of boys with PUV were treated endoscopically using a Holmium: YAG laser (1.2 J, 20 Hz, 800 μs). Feasibility was evaluated using operative time in minutes, spontaneous normal micturition after bladder catheter removal, and the duration of bladder catheterization in days in the absence of satisfactory micturition. Peri-operative complications were recorded. A VCUG was performed at 6 weeks postoperatively to exclude residual valves. Results: Since September 2018, 18 children with PUV were included. The median age at the time of endoscopic laser incision was 12 days (1 day-5 years). The median operative duration was 28 min (17–35). The urinary catheter was systematically removed on the first postoperative day. There were no intraoperative or anaesthesia-related complications. More specifically, no urethral injuries and no bleeding were recorded. No incomplete VUP incision was found on follow-up VCUG, and no endoscopic revision was necessary thus far, with a median follow-up of 44 months (6 months–60 months). Discussion: The use of the Holmium: YAG laser introduces new perspectives in the treatment of PUV. Its mechanism of action is considered a photothermic effect with a vapourization effect. The laser energy released by the Holmium: YAG source has a short tissue penetration distance and is strongly absorbed in an aqueous environment and therefore limits thermal tissue damage and favours early tissue re-epithelialization, reducing the risk of urethral stricture and decreasing postoperative oedema. The use of the laser in "incision" mode is the setting that most solicits the capacities of the laser (high energy, high frequency, and long pulse). The use of laser energy has the advantage of allowing tissue vapourization while ensuring maximal haemostasis and the possibility of introducing the laser fibre through the working channels of small, 6-Fr paediatric endoscopes. Conclusion: In our experience, endoscopic PUV incision using the Holmium: YAG laser appears to be a safe and efficient technique.